Long-Term Effect of Non-Selective Beta-Blockers in Patients With Rheumatoid Arthritis After Myocardial Infarction—A Nationwide Cohort Study - Liu, Sheng-Fu; Lee, Chih-Kuo; Huang, Kuan-Chih; Lin, Lian-Yu; Hsieh, Mu-Yang; Lin, Ting-Tse (Frontiers in Pharmacology, 2021)
Objectives: Rheumatoid arthritis (RA) is an independent nontraditional risk factor for incidence of myocardial infarction (MI) and post-MI outcome is impaired in the RA population. Use of beta-blockers improves the long-term survival after MI in the general population while the protective effect of beta-blockers in RA patients is not clear. We investigate the impact of beta-blockers on the long-term outcome of MI among RA patients. Methods: We identified RA subjects from the registries for catastrophic illness and myocardial infarction from 2003 to 2013. The enrolled subjects were divided into three groups according to the prescription of beta-blockers (non-user, non-selective, and β1-selective beta-blockers). The primary endpoint was all-cause mortality. We adjusted clinical variables and utilized propensity scores to balance confounding bias. Cox proportional hazards regression models were used to estimate the incidence of mortality in different groups. Results: A total of 1,292 RA patients with myocardial infarction were enrolled, where 424 (32.8%), 281 (21.7%), and 587 (45.5%) subjects used non-user, non-selective, and β1-selective beta-blockers, respectively. Use of beta-blockers was associated with lower risk of all-cause mortality after adjustment with comorbidities, medications (adjusted hazard ratio [HR] 0.871; 95% confidence interval [CI] 0.727–0.978), and propensity score (HR 0.882; 95% CI 0.724–0.982). Compared with β1-selective beta-blockers, treatment with non-selective beta-blockers (HR 0.856; 95% CI 0.702–0.984) was significantly related to lower risk of mortality. The protective effect of non-selective beta-blockers remained in different subgroups including sex and different anti-inflammatory drugs. Conclusion: Use of beta-blockers improved prognosis in post-MI patients with RA. Treatment with non-selective beta-blockers was significantly associated with reduced risk of mortality in RA patients after MI rather than β1-selective beta-blockers.